Comprehensive 5P framework for active aging using the ecological approach: an iterative systematic review - Azadeh Lak; Parichehr Rashidghalam; Phyo K. Myint; Hamid R. Baradaran (BMC, 2020)
Abstract Background "Active aging" is an inclusive term and has been defined from a variety of aspects in different domains throughout the literature. The aim of this review was to identify those aspects that play significant roles in building this concept using an ecological approach. Methods In this study, seven online databases, including JSTOR, Pub-Med, Web of Science, Google Scholar, ProQuest, EBSCO, and Scopus, were searched from 2002 to 2018 for both qualitative and quantitative articles published in English. Two reviewers independently found the related articles using the search terms "active aging" and "built environment" and included both "ageing" and "aging". Results Of 1500 records which passed the screening stage, 92 were eligible for inclusion in the review. A total of 15 subthemes were derived: (1) personal characteristics, (2) behavioral attitude, (3) land use, (4) access, (5) physical form, (6) cityscape/city image, (7) public open spaces, (8) housing, (9) social environment, (10) cultural Environment, (11) economic environment, (12) good governance, (13) physical health, (14) mental health, and (15) social health. Ecological themes of active aging can be defined as the 5P model: person, processes, place, prime, and policymaking. Conclusions The results of this study can shed light on different aspects of active aging. Also, the results emphasized the significance of the multidimensional nature of active aging, micro (person), meso (process), and macro systems (place and policymaking), based on health (prime) environments. Moreover, the results were based on the relationships between the person and the environment at the individual, interpersonal, and environmental levels, which can be used to conduct future studies and develop policies on aging populations.